2005
DOI: 10.1103/physreva.72.042331
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control-based efficient synthesis of building blocks of quantum algorithms: A perspective from network complexity towards time complexity

Abstract: In this paper, we demonstrate that optimal control algorithms can be used to speed up the implementation of modules of quantum algorithms or quantum simulations in networks of coupled qubits. The gain is most prominent in realistic cases, where the qubits are not all mutually coupled. Thus the shortest times obtained depend on the coupling topology as well as on the characteristic ratio of the time scales for local controls vs non-local (i.e. coupling) evolutions in the specific experimental setting. Relating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
200
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(205 citation statements)
references
References 48 publications
5
200
0
Order By: Relevance
“…Several OCT studies have shown that violating condition (3) by limiting the number of control variables [180] or the control period T [81,168,[170][171][172][173][174][175][176][177][178][179] can prevent the achievement of a globally optimal solution. In this section, we investigate the practical effects of imposing various types of constraints.…”
Section: Effects Of Severe Control Field Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several OCT studies have shown that violating condition (3) by limiting the number of control variables [180] or the control period T [81,168,[170][171][172][173][174][175][176][177][178][179] can prevent the achievement of a globally optimal solution. In this section, we investigate the practical effects of imposing various types of constraints.…”
Section: Effects Of Severe Control Field Constraintsmentioning
confidence: 99%
“…Special algorithms that facilitate successful optimization when the control field has significant spectral constraints have been introduced, for problems such as population transfer in a onedimensional asymmetric double well [169] and molecular alignment [166]. Other works have explored the effect of a specific constraint on OCT optimization; timeoptimal control, the problem of achieving a target objective in the minimum possible time, has received the greatest attention [81,168,[170][171][172][173][174][175][176][177][178][179], and constraints on the number of field components have also been investigated [180]. In this work, we perform extensive OCT simulations to evaluate constraints whose effects on the success of gradient optimization have not previously been examined, identifying values of each constrained parameter beyond which some or all of a set of searches fail to optimize.…”
Section: Introductionmentioning
confidence: 99%
“…[4] (see also [5,6,7,8,9,10,11,12,13,14,15,16,17,18]) presents time-optimal control algorithms to synthesize arbitrary unitary transformations on a system of two qubits. Further progress in the case of multiple qubits is reported in [5,10,16,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Given any unitary transformation G ∈ G, let t opt be the smallest possible time such that (a 1 , a 2 ) T ≺ r t opt (b 1 , b 2 ) T (22) and G =K 2 exp[a 1 (−iS β I x )+ a 2 (−iS α I x )]K 1 withK j ∈ K. Again, the KAK decomposition is not unique, and different KAK decompositions correspond to all values a ′ j = a j + 2πz j , where z j ∈ Z (see Sec. A 2).…”
Section: B the General Casementioning
confidence: 99%
“…the number of gates needed to reach the Haar distribution. In contraposition to the gate complexity, a new complexity concept for quantum algorithms has been proposed: the time complexity [19,20], understood as the physical time needed to perform such algorithm. The minimization of this time is as important, from the experimental point of view, as the gate complexity.…”
Section: Introductionmentioning
confidence: 99%